Plasma Levels of Endothelial Microparticles Bearing Monomeric C-reactive Protein Are Increased in Peripheral Artery Disease - Crawford, Jeffrey R. (J Cardiovasc Transl Res, 2016)
C-reactive Protein (CRP) as an indicator of cardiovascular disease (CVD) has shown limited sensitivity. We demonstrate that two isoforms of CRP (pentameric, pCRP and monomeric, mCRP) present in soluble form or on microparticles (MPs) have different biological effects and are not all measured by clinical CRP assays. The hsCRP assay did not measure pCRP or mCRP on MPs, whereas flow cytometry did. MPs derived from endothelial cells, particularly those bearing mCRP, were elevated in PAD patients compared to controls. The numbers of mCRP(+) endothelial MPs did not correlate with hsCRP measurements of soluble pCRP, indicating their independent modulation. In controls, statins lowered mCRP(+) endothelial MPs. In a model of vascular inflammation, mCRP induced endothelial shedding of MPs and was proinflammatory, while pCRP was anti-inflammatory. mCRP on endothelial MPs may be both an unmeasured indicator of, and an amplifier of, vascular disease, and its detection might improve risk sensitivity.